Decreasing Admissions to the NICU: An Official Transition Bed for Neonates. (February 2021) - Baker, Erika L.; Parker, Leslie A.; Alissa, Rana
Abstract : Background: Evidence supports the need to decrease healthcare costs. One approach may be minimizing use of low-value care by reducing the number of unnecessary neonatal intensive care unit (NICU) admissions through the use of official neonatal transition beds. Purpose: To evaluate whether transition beds decrease unnecessary NICU admissions and estimate the cost savings of this practice change. Methods: This retrospective chart review examined the records of all neonates of 350/7 weeks' gestational age and greater with birth weights of 2000 g and more admitted to a neonatal transition bed from January 1, 2017, to December 31, 2017. Outcomes evaluated were number of neonates returned to their mothers and an estimate of dollars saved for a 1-year period. Results: A total of 194 neonates were admitted to transition beds, which resulted in 144 NICU admissions averted. Respiratory distress was the most common reason for admission to transition beds. There was a statistically significant difference in length of stay in transition beds between neonates admitted to the NICU and those returned to couplet care after admission to transition beds (135.92 minutes vs 159.27 minutes; P = .047). There was no difference in gestational age based on admission to NICU or returned to couplet care (37.9 weeks vs 38 weeks; P = .772). The estimated cost savings was $3000 per neonate returned to couplet care totaling $432, 000 annually. Implications for Practice: The use of neonatal transition beds is a potential strategy to decrease unnecessary NICU admissions and reduce low value care. Implications for Research: Research regarding potential benefits of transition beds including the effect on hospital resources and low-value care at other institutions is needed. Additional research regarding potential benefits to the family including parent satisfaction and the effect of transition beds on rates of breastfeeding and skin-to-skin care is important.